Association of lymphocyte-to-C-reactive protein ratio with cerebral small vessel disease: a cross-sectional study based on dose-response analysis - Lin, Jie; Liu, Junyi; Luo, Qian; Zhuang, Jieying; Xiao, Ruiyan; Wang, Huijuan; Yang, Xudong; Wei, Xiaolan; Cai, Jiangping (Frontiers in Neurology, 2024)
ObjectiveWe investigated the relationship between lymphocyte-to-C-reactive protein ratio (LCR) and common imaging markers of cerebral small vessel disease (CSVD).MethodsData from 835 CSVD patients were analyzed using univariate and multivariate logistic regression to determine CSVD-associated factors. Multivariate models assessed the association between LCR and CSVD, including common imaging markers. Subgroup analysis by age, sex, smoking history, hypertension, lipid levels, and other factors was conducted. The receiver operating characteristic curve analysis and 10-fold cross-validation were performed to evaluate the predictive performance of LCR.ResultsLymphocyte-to-C-reactive protein ratio was independently associated with a decreased risk of CSVD (p < 0.001), indicating a protective role of LCR against CSVD. Among the imaging markers of CSVD, LCR in the highest quartile was negatively associated with moderate-to-severe white matter hyperintensities (WMH) (p = 0.002) and moderate-to-severe enlarged perivascular spaces (EPVS) (p < 0.001), but not with lacune (p > 0.05). The restrictive cubic spline analysis revealed a linear dose-response relationship between log-transformed LCR and the incidence of CSVD (Pnon-linear = 0.090) as well as moderate-to-severe WMH (Pnon-linear = 0.304), with a non-linear association with moderate and severe EPVS (Pnon-linear = 0.001). In the subgroup analyses, LCR remained a significant association with CSVD in most subgroups (p < 0.05). Notably, a significant correlation was observed between LCR and CSVD (p < 0.001) in the subgroups of non-smokers, those with neutrophil count ≤6.3 × 109/L, and with high-density lipoprotein cholesterol ≥1 mmol/L. No interaction effect was identified between the variables and the LCR (p > 0.1). The predictive capability of LCR for CSVD was confirmed through receiver operating characteristic curve analysis.ConclusionLymphocyte-to-C-reactive protein ratio is an independent protective factor for CSVD and is associated with lower WMH or EPVS burden but not lacune. Inflammation is involved in CSVD pathophysiology through multiple pathways, providing potential targets for CSVD intervention.